2013
DOI: 10.5812/ijhrba.11855
|View full text |Cite
|
Sign up to set email alerts
|

A Study on High-risk Premarital Sexual Behavior of College Going Male Students in Jamnagar City of Gujarat, India

Abstract: Background:The pre-marital sex and live-in relationship among young people are increasing at an alarming rate. Remote consequences of such high risk behaviors are increase in the incidence of STDs (including HIV), unsafe and illegal abortion, adolescent pregnancy and motherhood, single mother child/abandoned child, juvenile delinquency and many more.Objectives:The aim of this study was to investigate the high-risk sexual behaviors in depth, influenced by various factors including age at sexual debut, type of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
1
17
3
Order By: Relevance
“…The prevalence of premarital sexual practice in this systematic review and meta-analysis was lower than ndings of the study conducted in China, Nepal and Nigeria [2,3,53]. This systematic review and meta-analysis was also reported a more prevalent estimate compared with a study conducted in India and Vietnam [6,7]conducted on school youths. Figure4 Forest plots which describe factors associated with premarital sexual practices in Ethiopia 2006-2018…”
Section: Associated Factors Of Premarital Sexual Practices In Ethiopiacontrasting
confidence: 50%
See 2 more Smart Citations
“…The prevalence of premarital sexual practice in this systematic review and meta-analysis was lower than ndings of the study conducted in China, Nepal and Nigeria [2,3,53]. This systematic review and meta-analysis was also reported a more prevalent estimate compared with a study conducted in India and Vietnam [6,7]conducted on school youths. Figure4 Forest plots which describe factors associated with premarital sexual practices in Ethiopia 2006-2018…”
Section: Associated Factors Of Premarital Sexual Practices In Ethiopiacontrasting
confidence: 50%
“…Among youths who practiced premarital sexual practice, only very few numbers were continued as husband later on, while majority had sex with love even end up with prostitute [6]. Youths who begin early sexual activity are more likely to be exposed for high-risk of having multiple sexual partners [3,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of EPSB among Iranian female university students was estimated to be in a range from range from 4% to 10% (12)(13)(14). One study showed student have had pre-marital sex, 95% sex with student partners, and 14.5% with non-student partners (15).…”
Section: Introductionmentioning
confidence: 99%
“…(2) In a study done among college students of Gujarat, India, 14% of 450 participants gave history of premarital sex. (3) But premarital sex was found among 32% of young people of this study. Since the study was among STI clinic attendees, this may explain the higher percentage of risk behaviour found in this study.…”
Section: Discussionmentioning
confidence: 57%